Thermocoagulation as a Surgical Approach for the Treatment of Obsessive-Compulsive Disorder in Refractory Patients: Systematic Review - Chaves, Lucas Praxedes; Souza, Álef Ribeiro; Silva, Ledismar José da; Crivellaro, Laura de Lima; Silva, Marina Ferreira da (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2021)
Obsessive-compulsive disorder (OCD), a disabling chronic neuropsychiatric disease, entails high economic costs to society and has high morbidity and mortality rates. The first-line treatments for OCD are selective serotonin reuptake inhibitors and cognitive-behavioral therapy. However, this disorder has the highest refractory index to noninvasive treatment. Alternatively, ablative thermocoagulation neurosurgical techniques have shown efficacy and few adverse effects. The present systematic review aimed to identify validated protocols to observe the effectiveness of ablative procedures in the treatment of severe and refractory OCD, as well as their possible adverse effects and benefits. This review supports the effectiveness of ablative methods by presenting them as a safe non-experimental therapeutic option for cases of highly-refractory OCD. Additional relevant findings were the improvement in cognitive function, functional capacity, affective orientation, and quality of life, which contribute to the destigmatization of this surgical technique. Further controlled studies may lead to the individualization of recommendations of targets for ablative thermocoagulation.
Keywords: obsessive compulsive disorder; refractory; thermocoagulation; neurosurgery